Schools Surau and Their Relation to the Teaching of Islamic Education - Mohd Aderi Che Noh; Siti Adawiyah Mohd Adzmy (International Journal of Learning and Education, 2026)
This quantitative study examines teachers' perceptions of the roles and infrastructure of surau (school prayer halls) and the teaching of Islamic Education in surau at National Schools in Malaysia. It involved 500 Islamic Education teachers from five zones (North, East, Centre, South, and East Malaysia). The pilot study recorded a relatively high Cronbach's Alpha reliability value (0.989). Data were analyzed descriptively using mean, standard deviation, and percentages, and further tested using the t-test, one-way ANOVA, Pearson correlation, and multiple linear regression at a significance value of 0.05. Overall, the findings showed a mean of 4.39 for the surau's role, the highest among the variables, while teaching Islamic Education in the surau recorded an average mean (3.69) and surau infrastructure also recorded an average mean (3.95). The t-test and one-way ANOVA showed a significant difference between teaching Islamic Education at the surau and its infrastructure (p < .05). Physical and ergonomic aspects were also found to contribute significantly to the teaching of Islamic Education at surau in National Schools. The study showed that surau, together with their infrastructure, are capable of improving and upholding Islamic Education in National Schools. As a contribution, the study suggests that the 'Model Surau Sekolah Bersepadu' be implemented in teaching Islamic Education in National Schools in Malaysia.Keywords: Islamic Education, Surau, Infrastructure, Location, Gender, Ergonomic